2014
DOI: 10.1111/eth.12338
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Moonlight on Scopoli's Shearwater Calonectris diomedea Colony Attendance Patterns and Nocturnal Foraging: A Test of the Foraging Efficiency Hypothesis

Abstract: Moonlight is known to affect the nocturnal behaviour and activity rhythms of many organisms. For instance, predators active at night may take advantage from increased visibility afforded by the moon, while prey might regulate their activity patterns to become less detectable. Many species of pelagic seabirds attend their colony only at night, in complete darkness, avoiding approaching their nest sites under moonlight. This behaviour has been most often interpreted as an antipredator adaptation ('predation avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 68 publications
3
42
2
Order By: Relevance
“…Given that birds performed only short trips during early chick-rearing, the number of dives during the afternoon was higher during short trips than during long trips. The dive rates per hour recorded in this study differed from observations of Rubolini et al (2015) who noticed a peak of dive activity at 21:00 (local time) when we observed the minimum dive rates. This difference might be methodological, based on the estimation of dive occurrences using compass loggers.…”
Section: Effect Of Daytime and Sex On Foraging Effortcontrasting
confidence: 99%
See 3 more Smart Citations
“…Given that birds performed only short trips during early chick-rearing, the number of dives during the afternoon was higher during short trips than during long trips. The dive rates per hour recorded in this study differed from observations of Rubolini et al (2015) who noticed a peak of dive activity at 21:00 (local time) when we observed the minimum dive rates. This difference might be methodological, based on the estimation of dive occurrences using compass loggers.…”
Section: Effect Of Daytime and Sex On Foraging Effortcontrasting
confidence: 99%
“…Dive data from previous studies on Scopoli's shearwater are in line with our results: Grémillet et al (2014Grémillet et al ( ) recorded 9 ± 8 (2012 and 49 ± 47 (2013) dives per trip using TDRs during chick-rearing, while our algorithm recorded 84.7 ± 156.4 dives per trip in the same period. Rubolini et al (2015) recorded an average of 0.35 ± 0.02 dives per hour using compass loggers during chick-rearing. Compass loggers identified dives using temperature variations recording every 5 s. In the same reproductive phase, our algorithm identified 1.7 ± 1.6 dives per hour.…”
Section: Identification Of Divesmentioning
confidence: 99%
See 2 more Smart Citations
“…The lunar cycle is known to impact colony attendance in small nocturnal Procellariiformes (Mougeot & Bretagnolle 2000). In general, birds attend the colony more often on dark, new-moon nights, which is usually explained as an anti-predator behaviour (Rubolini et al 2014). The lunar cycle may also affect the foraging success of Bulwer's Petrels by influencing the sub-surface availability of mesopelagic fishes and squids (Hernandez-Leon et al 2002), which represent the bulk of their diet (Neves et al 2011).…”
mentioning
confidence: 99%